The Ethical Turn in Commodity Culture: Consumption, Care and the Other - Tania Lewis ([sic])
In a small courtyard at the University of Melbourne, there is an unprepossessing, somewhat makeshift looking outdoor café called KereKere. The coffee on offer is organic, Fair Trade, Rainforest alliance-branded and sustainable: a list of options we’ve increasingly come to expect even in corporate café chains such as Starbucks. But at this café, customers are also asked to decide how the profits from that sale are distributed every time they buy a coffee. As customers are handed their order, they are also presented with playing cards that allow them to choose from a list of causes where the café’s profits will go. The café thus operates in the spirit of ‘kerekere’, a Fijian custom in which a relative or neighbour can request something that is needed and it must be willingly given with no expectation of repayment. The café’s young ethically minded owner sees this process as fostering ‘a culture that promotes community wellbeing’. At this café, the traditional economic exchange associated with the purchase of a cup of coffee has been subtly moved into other territories through the introduction of questions of gift giving, and of responsibility, care and even love (as we see here, the café’s logo is a coffee cup with a series of hearts rising from it) into the exchange ritual. Such attempts by social justice-oriented businesses to reconfigure the privatized moment of spending as a communal act, thus positioning consumer choice as a site of responsibility, are increasingly commonplace in today’s marketplace. No longer purely associated with fringe politics or hippie lifestyles, terms such as ‘ethical’ and ‘responsible’ shopping and ‘conscience consumption’, are increasingly entering into the everyday language as well as the shopping experiences and practices of so-called ‘ordinary’ consumers.